Pengaruh Sikap Keuangan, Perilaku Keuangan, Dan Literasi Keuangan Terhadap Kinerja Keuangan Pada UMKM Di Kecamatan Pakis Kabupaten Malang - M, Tiara Nur; Mardani, Ronny Malavia; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to analyze the influence of financial attitudes, financial behaviors, and financial literacy on financial performance in MSMEs in Pakis District, Malang Regency. This type of research uses a quantitative method. The population in this study consists of culinary MSMEs located in Pakis District, with a sample size of 91 respondents and purposive sampling as the sampling technique. The data sources come from primary data through the distribution of questionnaires and using SPSS software version 25.0 as a data analysis tool. The results of the study show that financial attitudes and financial literacy have a significant positive effect on financial performance, while financial behavior does not have a significant positive effect on financial performance. Keywords: Financial Attitude, Financial Behavior, Financial Literacy, Financial Performance.